Ragna crimson. 9 - Kobayashi, Daiki (Manga artist) (Square Enix Manga & Books, 2023)
"After narrowly escaping a blitzkrieg attack by Woltekamui, the Lightning Claw Dragon, the surviving members of the Argentum Corps meet with a strange and fearsome new entity: a holy warrior of the mysterious Solarian order. Meanwhile, Ragna reunites with Crimson, but the encounter doesn't exactly go how either one of them had planned..."--Back cover.